Green Islamic Education: Integrating Environmental Ethics into Islamic Religious Education for Sustainable Development - Mahmoud Abdullah; Huzaiman Hushin; Salma Begum; Yousif Mahmadov; Abdallah El-Khatib (Ar-rayyan: Journal Of Islamic Education, 2025)
Environmental degradation has become one of the most pressing global challenges, requiring educational institutions to cultivate ecological awareness and responsible environmental behavior among students. Islamic Religious Education possesses strong theological foundations for environmental stewardship; however, these values remain insufficiently integrated into classroom instruction. This study aims to develop a Green Islamic Education framework that incorporates Islamic environmental ethics into the teaching and learning process. A qualitative design based on library research and multiple case studies was employed. Data were obtained through curriculum analysis, classroom observations, interviews with teachers, and institutional document reviews. The results demonstrate that integrating Qur’anic environmental values, prophetic traditions, project-based ecological activities, and community participation significantly enhances students’ environmental literacy, ecological responsibility, and sustainable lifestyles. The framework also encourages interdisciplinary collaboration aligned with Sustainable Development Goals (SDGs). The novelty of this study is the formulation of a comprehensive Green Islamic Education model that combines Islamic ecological theology, environmental education, and sustainability competencies within contemporary Islamic Religious Education